COVID-19: A Great Mime or a Trigger Event of Autoimmune Manifestations? - Fatone, Maria C. (Current Rheumatology Reviews, 2021)
Viruses can induce autoimmune diseases, in addition to genetic predisposition and environmental factors. Particularly, coronaviruses are mentioned among the viruses implicated in autoimmunity. Today, the world's greatest threat derives from the pandemic of a new human coronavirus, called “severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the responsible agent of coronavirus disease 2019 (COVID-19). First case of COVID-19 was identified in Wuhan, the capital of Hubei, China, in December 2019 and quickly spread around the world. This review focuses on autoimmune manifestations described during COVID-19, including pro-thrombotic state associated with antiphospholipid antibodies (aPL), acute interstitial pneumonia, macrophage activation syndrome, lymphocytopenia, systemic vasculitis, and autoimmune skin lesions. This offers the opportunity to highlight the pathogenetic mechanisms common to COVID-19 and several autoimmune diseases in order to identify new therapeutic targets. In a supposed preliminary pathogenetic model, SARS-CoV-2 plays a direct role in triggering widespread microthrombosis and microvascular inflammation, because it is able to induce transient aPL, endothelial damage and complement activation at the same time. Hence, endothelium might represent the common pathway in which autoimmunity and infection converge. In addition, autoimmune phenomena in COVID-19 can be explained by regulatory T cells impairment and cytokines cascade.
Keywords: antiphospholipid antibodies